Risk of invasion and disease transmission by the Australasian freshwater snail Orientogalba viridis (Lymnaeidae): a field and experimental study - Vázquez, Antonio A. (2024)
Biological invasions pose risks to the normal functioning of ecosystems by altering the structure and composition of several communities. Molluscs stand out as an extensively studied group given their long history of introduction by either natural or anthropogenic dispersal events. An alien population of the lymnaeid species Orientogalba viridis was first sighted in 2009 in southern Spain. In its native range (Australasian), this species is one of the main intermediate hosts of Fasciola hepatica, a major worldwide trematode parasite largely afecting humans, domestic animals and wildlife. We collected field populations of O. viridis from its native (Malaysia) and invaded (Spain) ranges. We performed detailed morphoanatomical drawings of the species and screened for natural infection of parasites. Individuals were molecularly characterized using ITS2 for comparison with existing sequences in a fine phylogeography study. We founded experimental populations at two different conditions (tropical, 26 °C and temperate, 21 °C) to study the life-history traits of exposed and non-exposed individuals to different F. hepatica isolates. We found a 9% natural prevalence of trematode infection (98% similarity with a sequence of Hypoderaeum conoideum [Echinostomatidae]) in the Spanish field population. The haplotypes of O. viridis found in our study from Spain clustered with Australian haplotypes. Experimental infection with F. hepatica was successful in both experimental conditions but higher in tropical (87% prevalence) than in temperate (73%). Overall lifespan, however, was higher in temperate conditions (mean 32.5±7.4 weeks versus 23.3±6.5) and survivorship remained above 70% during the first 20 weeks. In parasite-exposed populations, life expectancy dropped from an overall 37.75 weeks to 11.35 weeks but still doubled the time for initial cercariae shedding. Cercariae shedding started at day 23 post exposure and peaked between days 53 and 67 with an average of 106 metacercariae per snail. Whether O. viridis will succeed in Europe is unknown, but the odds are for a scenario in which a major snail host of F. hepatica occupy all available habitats of potential transmission foci, ravelling the epidemiology.